Rediscovery of Hansenomysis lucifugus (Faxon, 1893) (Crustacea, Mysida, Petalophthalmidae) in the eastern Pacific - Hendrickx, Michel E.; Hernández-Payán, José-Carlos (Zootaxa, 2020)
The deep-water mysid, Hansenomysis lucifugus (Faxon, 1893), previously known only from the type locality off the Galapagos Islands, is rediscovered off western Mexico. A complete description is provided based on this new material. The new records correspond to a series of 15 adult females and increase the known distribution of this species by over 30° of latitude to the north, to 30°51.26’N–116°42.18’W. Although no precise depth range in the water column is known for this species, it has been collected in localities where total depth was at least 1848 m.